Preparation of BiOBr lamellar structure with high photocatalytic activity by CTAB as Br source and template - Shang, Meng; Wang, Wenzhong; Zhang, Ling (Journal of hazardous materials, 2009)
Visible-light-induced photocatalyst BiOBr has been synthesized by a hydrothermal method, in which cetyltrimethylammonium bromide (CTAB) acted not only as the template but also the Br source. A possible formation mechanism of BiOBr lamellar structure with the assistance of CTAB under hydrothermal condition was proposed. The photocatalytic activities were evaluated by the degradation of methyl orange (MO) at pH 4.5 under visible-light irradiation ( λ > 420 nm). The lamellar BiOBr prepared in 100 mL CTAB solution with the molar ratio of CTAB/Bi(NO 3) 3 ( R) = 2:1 at the hydrothermal temperature of 160 °C for 24 h exhibited excellent visible-light-driven photocatalytic efficiency, which was up to 96% within 120 min. This was about four times higher than that of the BiOBr synthesized by KBr. After five recycles, the catalyst did not exhibit any significant loss of photocatalytic activity, confirming the photocatalyst is essentially stable. Close investigation revealed that the size, the band gap, and the structure of as-prepared BiOBr affected the photocatalytic activities.